Clinical Pharmacology of Delafloxacin in Patients With Hepatic Impairment. (14th October 2016) - Hoover, Randall; Marbury, Thomas C.; Preston, Richard A.; Quintas, Megan; Lawrence, Laura E.; Paulson, Susan K.; Luke, David R.; Cammarata, Sue K.
Abstract: Delafloxacin is a novel anionic fluoroquinolone with robust activity against Gram‐positive, Gram‐negative, atypical, and anaerobic bacteria, including methicillin‐resistant S aureus . Delafloxacin is currently being studied for the treatment of acute bacterial skin and skin structure infections and community‐acquired pneumonia. This was a phase 1, open‐label pharmacokinetic and safety study of a single intravenous dose of 300 mg delafloxacin in subjects with mild, moderate, and severe hepatic impairment (Child‐Pugh class A, B, and C, respectively) compared with matched healthy controls. The effects of hepatic impairment were assessed by ANOVA of log‐transformed values for AUC0‐∞, Cmax, and systemic clearance, with hepatic group as a fixed effect. Mean AUC0‐∞ and Cmax in each impairment group were not significantly different from those of the pooled healthy subjects ( P > 0.05). The 90% confidence interval (CI) of the percentage ratios of least‐squares means of AUC0‐∞ did not indicate significant differences between the impairment groups and pooled healthy controls: Child‐Pugh class A (mild) 114.4 (CI: 95.6, 137.0), Child‐Pugh class B (moderate) 114.8 (CI: 95.9, 137.4), and Child‐Pugh class C (severe) 115.1 (CI: 96.1, 137.8). A single IV infusion of delafloxacin was generally well tolerated in all treatment groups. The exposure and clearance of delafloxacin in subjects with mild, moderate, or severe hepatic impairment did not significantly differ from those of pooled, matched healthy subjects. Based on these pharmacokinetic data, dose adjustment of delafloxacin in the presence of hepatic impairment is not needed.